The prediction of the small for gestational age fetus with the head circumference to abdominal circumference (HC/AC) ratio: a new look at an old measurement. Issue 2 (June 2015) - Quinton, Ann; Cook, Colleen; Peek, Michael
Abstract: Introduction: The small for gestational age (SGA) fetus is at a higher risk of adverse events throughout life. Third trimester ultrasound measurements are poor at predicting SGA at delivery. We aimed to determine if ultrasound biometric growth parameters at 28–32 weeks of gestation could predict SGA, defined as birth weight below the 10th percentile. Method: The relationship between fetal biometry and SGA at birth was examined using various statistical analyses. This prospective cross‐sectional study of 41 women (smokers n  = 21; non‐smokers n  = 20) had a 20% SGA incidence (8/41). Results: We demonstrated an increase in the head circumference (HC)/abdominal circumference (AC) ratio correlated with a decrease in birth weight percentile ( r  = −0.528, P  < 0.001). The HC/AC ratio was the best predictor of SGA and was significantly higher at 1.105 ± 0.037 (mean ± SD) for SGA neonates compared with 1.067 ± 0.039 for appropriate‐for‐gestational‐age neonates ( P  = 0.02). A cutoff value of 1.067 derived from the receiver operating characteristic curve gave a sensitivity of 88% and specificity of 52% with area under the curve equal to 0.742 ( P  = 0.04, Chi‐square). Discussion: An increased HC/AC ratio at 28–32 weeks was a sensitive predictor of SGA at delivery. The HC/AC ratio may prove to be a useful marker for SGA with larger studies necessary to confirm these findings.